Brazilian version of the Mattis dementia rating scale: diagnosis of mild dementia in Alzheimer's disease - Cláudia S. Porto; Helenice Charchat Fichman; Paulo Caramelli; Valéria S. Bahia; Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: To verify the diagnostic accuracy of the Brazilian version of the Mattis Dementia Rating Scale (DRS) in the diagnosis of patients with mild dementia in Alzheimer's disease (AD); to verify the interference of the variables age and schooling on the performance of the DRS. METHOD: The DRS was administered to 41 patients with mild AD and to 60 controls. In order to analyze the effects of age and schooling on the performance of the tests, patients and controls were separated into three age groups and three levels of schooling. RESULTS: The cutoff score of 122 showed a sensitivity of 91.7 % and specificity of 87.8 %. Age and schooling interfered in the DRS total score and in the scores of its subscales. CONCLUSION: The DRS showed good diagnostic accuracy in the discrimination of patients with mild AD from the control individuals. In the sample examined, the effects of schooling were more marked than age.